The folksong "Anastacio Pilakan" in Barangay Bagacay, Ibajay, Aklan. - Franco, Cyna Marie Amancio (2012.)
Folksongs reflect the culture or way of life of a group of individuals and it is being passed down from one generation to another through word of mouth. This pioneering study entitled ?The Folksong ?Anastacio Pilakan? in Barangay Bagacay, Ibajay, Aklan? was undertaken to document the lyrics and performance of the folksong so that the succeeding generations will be able to know and sing it. This study was also undertaken to draw some inferences or conclusions as to the significance of folksongs in unraveling local history and culture of the Ibajaynons. Old and native residents of Brangay Bagacay, Ibajay, Akalan as well as other Ibajaynons who had knowledge about the folksong functioned as the study?s key informants. The findings of the study revealed that the lyrics of folksong ?Anastacio Pilakan? provide a glimpse of the lifeways or culture of the Ibajaynons and performing the folksong with choreography and musical accompaniment is an effective way or method of passing the folksong to the next generation. It can be concluded that folksongs are mediums that can be used to learn the culture of a specific group of individuals.
Research Project (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2012.
Keywords: Folksongs -- Research